Production and characterisation of pva/whey protein/hydroxyapatite/gentamicin loaded scaffolds for bone tissue engineering applications - GÜNDÜZ, OĞUZHAN; CESUR, SÜMEYYE (My University, 2022)
3D printing technology is an approach used in health and it can be a pioneer by making progress in the near future [1]. 3D printers will be of great importance in the production of organs that can replace diseased or damaged tissues. Bone tissue engineering is an innovative treatment method to treat bone defects. In this treatment method, healthy tissues are expected to replace damaged tissues for the treatment of damaged tissues. For healthy tissues to be implanted, they are expected to be biocompatible and have the same physical, chemical and mechanical properties as damaged tissues [2]. The materials used should not have a toxic effect on the body, and the materials should also be suitable for printing for the biofunctional ink of the 3D printer. In this study, a new approach for bone tissue engineering is considered by using polyvinyl alcohol (PVA), whey protein isolate (WPI), hydroxyapatite (HA) and gentamicin (GEN). Control group (without gentamicin), and containing 12 mg gentamicin scaffolds were fabricated with 3D printing technology and characterisation tests were performed. The characterization of the scaffolds was carried out with Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscopy (SEM), X-Ray Diffraction (XRD) and compression test. The average pore sizes of the PVA/WPI/HA and PVA/WPI/HA/12GEN composite scaffolds was 716.25 ± 101.17 μm and 675.55 ± 60.71 μm, respectively. With the addition of GEN to composite scaffolds, a decrease in average pore size was observed. Compression test results showed that the compressive strength decreased from 1.28 MPa to 1.22 MPa with the addition of GEN to the composite scaffolds. Biocompatibility of PVA/WPI/HA and PVA/WPI/HA/12GEN composite scaffolds was determined with the MTT test. The test results showed that the fabricated composite scaffolds were non-toxic and cellular growth was provided. Gentamicin loaded composite scaffolds were successfully fabricated with 3D printing technology. The fabricated scaffolds have great potential to treat damaged tissue and cells for bone tissue engineering applications.
Keywords: Sağlık Bilimleri; Mühendislik ve Teknoloji; Health Sciences; Engineering and Technology; Klinik Tıp (MED); Mühendislik, Bilişim ve Teknoloji (ENG); Clinical Medicine (MED); Engineering, Computing & Technology (ENG); 3D Printing Technology; Bone Tissue Engineering; Drug Release; Hydroxyapatite; Gentamicin